Boron‐Doped PdCuAu Nanospine Assembly as an Efficient Electrocatalyst toward Formic Acid Oxidation. Issue 11 (3rd February 2020) - Wang, Hongjing; Qian, Xiaoqian; Liu, Songliang; Yin, Shuli; Xu, You; Li, Xiaonian; Wang, Ziqiang; Wang, Liang
Abstract: Control of the composition and morphology of Pd‐based electrocatalysts is a promising strategy for the development of efficient direct formic acid fuel cells. Herein, a two‐step method is presented for the design of B‐doped PdCuAu nanospine assemblies (B‐PdCuAu NAs) using NaBH4 as the boron dopant. The boron content can be tailored easily by tuning the reaction time, and an optimal boron content is beneficial to promote the formic acid oxidation reaction. Such B‐PdCuAu NAs exhibit superior mass and specific activities to commercial Pd black and PdCuAu NAs in alkaline solution. The excellent catalytic performance of B‐PdCuAu NAs may arise from the increase in surface active sites and the electronic effect of boron modification. This work provides a facile synthesis of the B‐doped metallic catalysts and highlights the boron modification in improving their performance as anode electrocatalysts for fuel cells. Abstract : Boron‐doped electrocatalysts : Boron‐doped PdCuAu nanospine assemblies are synthesized using NaBH4 as the boron dopant. This structure can provide sufficient surface active sites and the electronic effect. Therefore, such catalysts exhibit excellent mass and specific activities for the formic acid oxidation reaction in acidic solution (see scheme).